Performance of summer cover crops and influence on soil attributes in a demonstrative unity in Southwest Paraná (Research, Society and Development, 2020)
The cultivation of cover plants in southern Brazil is predominant in the winter period, although there are species adapted for the summer period, they are limited as information on their behavior for the region. Thus, the objective was to evaluate the development of summer fabáceas, at different sowing times and their effects on the N content and soil density (Ds). The experiment was implemented in 2010, with 10 species of cover plants, sown in five seasons, from November to March of each year. In the 2013/2014, 2014/2015 and 2015/2016 crops, the dry matter (MS) of cover crops was determined, in the last period the tissue nitrogen (N) content, availability of N and soil density (Ds). The plants had the highest MS production in the first sowing seasons and the highest N content in tissue when sown in March, however the largest source of N in the area occurs in the first sowing seasons, ranging from 92 to 255 kg N ha-1. The highest levels of N in any soil were found in the superficial layer, except for the crotalaria ocroleuca, which had the highest average N content in the 0.05-0.10 m layer. The lowest average density value was found in the superficial layer, 1.02 Mg m-³, and the highest value in the 0.05-0.10 m layer, 1.23 Mg m-³, for the species of pork beans and gray mucuna. Cover crops have the maximum potential for development when sown in November and December.